If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -5) = 3 Reorder the terms: -3(-5 + x) = 3 (-5 * -3 + x * -3) = 3 (15 + -3x) = 3 Solving 15 + -3x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -3x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = 3 + -15 -3x = 3 + -15 Combine like terms: 3 + -15 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| 8n+16=4n | | h(x)=x^3-4 | | i(7+9i)(7-9i)=0 | | 2x+5-4(x+1)=6x+8 | | 2x+4=6x-7 | | 16a+18b+5c+5c-4b-2a= | | 0.75x+0.05(20-x)= | | 42=3(2w-3h) | | 16+r=4(r+1) | | 41x(x)-12x+48=4x(x)(x)(x)-3x(x)-64x-48 | | 2(x+1)+4(4x+5)=92 | | X+3x=x+x+11 | | 66x+2484x-73=51(50x+40) | | 41x(x)-12x+48=4x(x)(x)(x)-3x(x) | | 3(1.5c+4)=-1 | | 41x(x)-12x+48=4x(x)(x)(x) | | (3x+1)=85 | | 8-8*2+3=0 | | 19x+.5ax=x+9 | | 3(3x+4)+97=11x+10-2x+99 | | 7x-y=43 | | 108+6x=180 | | 6(x+1)=6+7x | | 14p+15q+p-5q-7p= | | 5(c+3)=2(2c+11) | | 0.16(12)+0.04x=0.08(18+x) | | -2(6y-6)-y=-3(y-3) | | 4(x+6)-2(5-7x)= | | 11-5x=-7x+17 | | 4x-2y-12=0 | | 8x+6=abc | | -6=1-2n+5 |